2017
DOI: 10.1111/jbi.13132
|View full text |Cite
|
Sign up to set email alerts
|

Mountains as barriers to gene flow in amphibians: Quantifying the differential effect of a major mountain ridge on the genetic structure of four sympatric species with different life history traits

Abstract: Aim To test the role of mountains as barriers to gene flow in co‐distributed taxa with different life history traits. Location Sierra de Guadarrama, Central Spain. Methods We used larval genotypes of four amphibian species (Epidalea calamita, Hyla molleri, Pelophylax perezi and Pelobates cultripes) sampled on northern and southern slopes of Sierra de Guadarrama to describe genetic structure with FST, migration rates per generation, clustering algorithms and resistance by elevation surfaces. We also recorded in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 70 publications
2
45
0
Order By: Relevance
“…While our results contradict the conclusions of Zhan et al (2009), they are consistent with a large body of literature that has implicated mountains in the obstruction of gene flow for amphibians (e.g. Funk et al, 2005;Spear et al, 2005;Garcia, Ivy & Fu, 2017;S anchez-Montes et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…While our results contradict the conclusions of Zhan et al (2009), they are consistent with a large body of literature that has implicated mountains in the obstruction of gene flow for amphibians (e.g. Funk et al, 2005;Spear et al, 2005;Garcia, Ivy & Fu, 2017;S anchez-Montes et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…Roads and rivers have frequently been detected to impede amphibian dispersal (e.g. Lougheed et al , ; Crosby et al , ; Li et al , ), and perhaps more prominently, mountain ranges are considered significant genetic barriers and are assumed to be a major contributor to population structure in amphibians (Lougheed et al , ; Funk et al , ; Spear et al , ; Sánchez‐Montes et al , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, as observed in birds, butterflies, and plants (e.g., Li et al, ; Manish & Pandit, ; Martens et al, ; Xie et al, ), all lineages of Himalayan spiny frogs recorded at present would have dispersed from east to west or would have appeared during the potential range expansion along the Greater Himalaya. Thus, they must have been able to cross the many north–south stretching mountain ranges and the epigenetic transverse valleys, by which the Himalaya has always been intersected and that might form effective barriers to dispersal of amphibians (Sánchez‐Montes, Wang, Ariño, & Martínez‐Solano, ; Zhou et al, ). Relating thereto, the phylogenetic placement of the clade from the NW Himalaya is of particular interest.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, a role of ecology cannot be excluded. Recent studies have shown that fossorial species tend to have low dispersal abilities and smaller geographic distributions than nonfossorial frogs (Eggert, ; Penner & Rödel, ; Sánchez‐Montes, Wang, Ariño, & Martínez‐Solano, ; Székely, Cogălniceanu, Székely, & Denoël, ) and it is thus possible that fossoriality played a role in the limited distribution of the different linages in L. gramineus .…”
Section: Discussionmentioning
confidence: 99%